Responsibility of PPAT in Preventing Transfer of Land Rights that Violates the Principle of Prudence - Rokhman, Moh. Lutfi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In every land sale and purchase transaction, the existence of a Land Deed Official (PPAT) plays a key role. PPAT is not only a registrar, but also a guarantor of the legality of the land rights transfer process. One of the fundamental principles that must be upheld by PPAT is the principle of caution, namely a professional attitude to always check the validity of documents and the legality of objects before making a deed. However, in practice, it is not uncommon to find PPATs who ignore this principle. For example, making a deed for land that is still in dispute, does not have a certificate, or using the identity of an unauthorized party. Violations such as this not only harm the profession, but also have an impact on legal and financial losses for the parties involved. Therefore, it is important to examine more deeply the responsibilities of PPAT in preventing violations of the principle of caution. The PPAT is required to read the deed to the relevant parties and provide an explanation regarding the contents and purpose of making the deed, the PPAT deed must be read/explained to the parties in the presence of at least 2 (two) witnesses before being signed immediately by the parties, witnesses and the PPAT. One of the principles of caution is regulated in Article 22 of Government Regulation Number 37 of 1998 as amended by Government Regulation Number 28 of 2006 concerning Amendments to Government Regulation Number 37 of 1998 concerning Regulations on the Position of Deed Making Officials that the PPAT Deed must be read/explained to the parties in the presence of at least 2 (two) witnesses before being signed immediately by the parties, witnesses and the PPAT. Therefore, if the PPAT does not use the principle of caution, then the legal consequences of the deed made by the PPAT can be canceled by the party who feels aggrieved and can even go to court.